Effect of Alkaline and Drought Stress on Growth and SOD (Superoxide dismutase) Content in Basil Plant (Ocimum americanum L.) - Anindita Della Rosa Riyadi; Dwi Umi Siswanti (UIN Sunan Gunung Djati Bandung, 2022)
Basil plant (Ocimum americanum L.) is a fragrant annual plant widely cultivated by the people in Indonesia because it is useful and commercial. Previous research on salinity and drought stress in basil affects growth and development plant, cell turgor pressure, and the anatomical structure of the plant. However, research on the effect of alkalinity and drought stress in basil plants has not been carried out. Therefore, this study was conducted to determine the effect of variations in alkaline and drought stress on the growth and superoxide dismutase (SOD) content of basil plants. Alkalinity stress was carried out by variations of dolomite (D) doses which is divided into four levels, namely D1, D2, D3, and D4 (0 grams/pot, 100 grams/pot, 150 grams/pot, and 200 grams/pot) and variations of drought stress were divided into four types of field capacity, namely A1, A2, A3, and A4 (25%, 50%, 75%, and 100%). Parameters measured were plant height, leaf length and width, number of leaves, fresh and dry weight, SOD content, and environmental parameters. The growth of the basil plant (O. americanum L.) decreased after being given drought stress at a field capacity level of 25%, while the SOD content of basil (O. americanum L.) did not differ significantly but increased with the increase in dolomite doses and field capacity given.